High-strength artificial stone and preparation method thereof

By optimizing the formula and carbonation and curing process of artificial stone slurry, CO2 is used to generate calcium carbonate and magnesium carbonate crystals to fill pores, combining the reaction of polyphosphate and silica fume to generate hydrated silica gel, and fiber enhances flexibility, solving the problem of current The artificial stone prepared by steel slag in technology has problems with strength and surface roughness, achieving high strength and delicate and smooth effects.

CN119241182AInactive Publication Date: 2025-01-03FOSHAN DONGPENG CERAMIC +4

Patent Information

Application Number
CN202411373954.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the artificial stone prepared with steel slag has poor strength and rough surface and insufficient carbonation degree, which affects its compressive and flexural strength. The low hydration activity of steel slag leads to delayed expansion and cracking, affecting volume stability.

Method used

Using high-strength artificial stone slurry formula, including steel slag, cement, calcium magnesium sand, calcium carbonate whiskers, polyphosphate, silica fume and fiber, the pores are filled with CO2 during the carbonation and maintenance process. , improve strength, and promote its dissolution by complexing polyphosphate with Ca2+ and Mg2+. Silica fume forms hydrated silica gel and bonds with calcium-magnesium sand aggregate, and fibers form a mesh structure to enhance flexibility.

Benefits of technology

The high-strength artificial stone surface is achieved with a delicate and smooth compressive strength ≥130MPa and a flexural strength ≥22MPa, which solves the problem of delayed expansion and cracking caused by low hydration activity of steel slag, and improves the volume stability and aesthetics of artificial stone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005068255930000141
    Figure BDA0005068255930000141
Patent Text Reader

Abstract

The invention discloses a high-strength artificial stone which is obtained by carbonating, curing and curing artificial stone slurry, the artificial stone slurry is prepared from the following raw materials in parts by mass: 40 to 60 parts of steel slag, 2 to 10 parts of cement, 70 to 120 parts of calcium magnesia, 0.04 to 0.12 part of calcium carbonate whisker, 0.01 to 0.03 part of polyphosphate, 0 to 10 parts of silica fume, 1 to 2 parts of fiber and 8 to 10 parts of water. The chemical components of the steel slag comprise silicon dioxide, magnesium oxide and calcium oxide; the mineral components of the steel slag comprise tricalcium silicate, beta-type dicalcium silicate, gamma-type dicalcium silicate, free calcium oxide and free magnesium oxide. According to the high-strength artificial stone provided by the invention, the artificial stone is fine and smooth in surface and relatively high in strength, and actual use requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial stones, and in particular to a high-strength artificial stone and a preparation method thereof. Background Art

[0002] Artificial stone is a decorative material made from raw materials such as cement, admixtures, quartz sand or calcium carbonate through high temperature and high pressure. It not only has the beautiful texture of natural stone, but also has excellent properties such as wear resistance, high temperature resistance and corrosion resistance. It is widely used in many fields such as home decoration, commercial places and medical facilities.

[0003] Steel slag generated in industrial production is a solid waste. Its large accumulation not only occupies precious land resources, but also may cause environmental pollution and other problems. In order to promote resource recycling, reduce production costs and alleviate environmental pressure, researchers have begun to explore new ways to use steel slag to prepare artificial stone. Among them, the chemical components of steel slag include silicon dioxide, magnesium oxide and calcium oxide, etc.; magnesium oxide mainly exists in the form of free calcium oxide, and magnesium oxide mainly exists in the form of free magnesium oxide; at the same time, the chemical component calcium oxide of steel slag can also form tricalcium silicate (C3S), β-type dicalcium silicate (β-C2S), and γ-type dicalcium silicate (γ-C2S) with its component silicon dioxide. In addition, the chemical components calcium oxide and magnesium oxide in steel slag can also form FeO-CaO-MgO-MnO (RO phase) with other chemical components, so that the mineral components in steel slag are mainly tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide, free magnesium oxide, FeO-CaO-MgO-MnO solid solution, etc. Since tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide and free magnesium oxide in steel slag have certain hydration activity and carbonation activity, it is beneficial to promote the use of steel slag in the preparation of artificial stone.

[0004] However, the prior art of using steel slag to prepare artificial stone has the following defects: (1) It is difficult to carbonate tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, and Ca in free calcium oxide. 2+ and Mg in free magnesium oxide 2+ Fully participate in the carbonation reaction (i.e. Ca in steel slag 2+ and Mg 2+The dissolution degree is limited), resulting in insufficient carbonation of steel slag, which in turn affects the strength of artificial stone; (3) The hydration activity of free calcium oxide and free magnesium oxide in steel slag is low and the content is large. Its continuous slow hydration in the environment not only causes delayed expansion and cracking of artificial stone, bringing serious volume stability problems, but also causes the free calcium oxide and free magnesium oxide in steel slag to be unable to be fully utilized, affecting the strength of artificial stone (3) The particle size and shape of steel slag are irregular, and during the carbonation and hydration process, steel slag is easily solidified to form uneven crystals, making the surface of artificial stone relatively rough, affecting the appearance and use effect. That is, the artificial stone made from steel slag in the prior art has poor strength and a relatively rough surface, which is difficult to meet actual use requirements. Summary of the invention

[0005] The purpose of the present invention is to provide a high-strength artificial stone, which not only has a fine and smooth surface but also has high strength to meet actual use requirements.

[0006] Another object of the present invention is to provide a method for preparing high-strength artificial stone. The preparation method is simple and easy to operate, ensuring that the obtained artificial stone has a compressive strength of ≥130MPa and a flexural strength of ≥22MPa. The surface is not only fine and smooth, but also has high strength.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A high-strength artificial stone obtained by carbonation, curing and solidification of artificial stone slurry;

[0009] Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 2-10 parts of cement, 70-120 parts of calcium magnesium sand, 0.04-0.12 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 0-10 parts of silica fume, 1-2 parts of fiber and 8-10 parts of water;

[0010] The chemical components of the steel slag include silicon dioxide, magnesium oxide and calcium oxide; the mineral components of the steel slag include tricalcium silicate, beta-type dicalcium silicate, gamma-type dicalcium silicate, free calcium oxide and free magnesium oxide.

[0011] Furthermore, the particle size of the steel slag is less than 75 μm, and the specific surface area is greater than 350 m 2 / g.

[0012] Furthermore, calculated by mass percentage, the chemical composition of the steel slag includes 12-14% silicon dioxide, 40-45% calcium oxide, 3-5% magnesium oxide, 3-5% aluminum oxide, 20-25% iron oxide, 4-6% manganese oxide, 1-2% titanium dioxide, 0-1% potassium oxide and 2-4% phosphorus pentoxide.

[0013] Further, the fibers include steel fibers, mineral fibers and organic fibers;

[0014] The mineral fibers include any one or more combinations of chopped basalt fibers, glass fibers and carbon fibers;

[0015] The organic fiber includes any one or more combinations of polyethylene fiber, polypropylene fiber, polyoxymethylene fiber and polyester fiber.

[0016] Furthermore, calculated by mass percentage, the calcium-magnesium sand includes 0-30% of Class I sand of 26-40 meshes, 40-60% of Class II sand of 40-70 meshes, 15-30% of Class III sand of 70-120 meshes, and 10-25% of Class IV sand of 120-200 meshes.

[0017] Furthermore, the polyphosphate includes any one of sodium pyrophosphate, potassium pyrophosphate, sodium tripolyphosphate, potassium tripolyphosphate, sodium hexametaphosphate and potassium hexametaphosphate.

[0018] Furthermore, according to the mass ratio, the mixing ratio of water to cement in the artificial stone slurry is (0.1-0.14):1;

[0019] The mixing ratio of calcium magnesium sand to cement in the artificial stone slurry is (0.8-1.5):1.

[0020] A method for preparing a high-strength artificial stone, characterized in that it is used to prepare the above-mentioned fine, smooth and high-strength artificial stone, comprising the following steps:

[0021] A. dissolving a formulated amount of cement, calcium carbonate whiskers, and silica fume in a part of the formulated amount of water, and stirring evenly to obtain a first mixture;

[0022] B. uniformly mixing the remaining amount of water and polyphosphate to obtain a second mixture;

[0023] C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly;

[0024] D. Pour the artificial stone slurry into the mold and press it into shape to obtain the intermediate product;

[0025] E. The intermediate product is subjected to carbonation curing and then solidified to obtain a high-strength artificial stone, wherein the thickness of the artificial stone is 10 to 40 mm, the compressive strength is ≥130 MPa, and the flexural strength is ≥22 MPa.

[0026] Furthermore, in step E, the curing temperature of the carbonation curing is 40-80° C., the curing time is 2-72 h, the curing pressure is 0.1-0.4 MPa, and the purity of CO2 is 20-99.9%.

[0027] Furthermore, in step D, the pressure of the compression molding is 8 to 25 MPa.

[0028] The technical solution provided by the present invention may include the following beneficial effects:

[0029] 1. During carbonation curing, gaseous CO2 quickly dissolves in the slurry to form carbonic acid, which then dissociates to form bicarbonate ions and carbonate ions; calcium hydroxide generated by free calcium oxide in an aqueous environment reacts with bicarbonate ions / carbonate ions to form calcium carbonate crystals, and magnesium hydroxide generated by free magnesium oxide in an aqueous environment reacts with bicarbonate ions / carbonate ions to form magnesium carbonate crystals, so that free calcium oxide and free magnesium oxide in the steel slag are quickly and massively eliminated, thereby not only eliminating the hidden danger of delayed expansion and cracking caused by the slow hydration of free calcium oxide and free magnesium oxide, but also the generated calcium carbonate crystals and magnesium carbonate crystals can improve the strength of artificial stone by filling pores and compacting the matrix. In addition, in an aqueous environment, the mineral components of the steel slag, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate, can react with bicarbonate ions / carbonate ions to form silica gel, which can better wrap and bond the calcium-magnesium sand aggregate in the artificial stone slurry formula to improve the strength of the artificial stone.

[0030] 2. As a chelating agent, polyphosphate can chelate with Ca2+ and Mg2+, thereby weakening the Ca-O bond and Mg-O bond in the mineral components of steel slag, and promoting the dissolution of Ca2+ and Mg2+ in the slurry, so that the Ca2+ and Mg2+ in the steel slag can participate in the carbonation reaction as much as possible, improve its carbonation degree, and thus increase the strength of artificial stone. At the same time, it also further eliminates the delayed expansion and cracking caused by the slow hydration of free calcium oxide and free magnesium oxide.

[0031] 3. Silica fume is added to the artificial stone slurry formula. The silicon dioxide in the silica fume is tiny spherical and has high reaction activity. It can not only react with the calcium hydroxide generated by free calcium oxide, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate in the steel slag in an aqueous environment to form hydrated calcium silicate gel, but also react with the magnesium hydroxide generated by free magnesium oxide in an aqueous environment to form hydrated magnesium silicate gel. The hydrated calcium silicate gel and hydrated magnesium silicate gel can better wrap and bond the calcium-magnesium sand aggregate in the artificial stone slurry formula, which is beneficial to improve the strength of the artificial stone.

[0032] 4. The fiber itself has excellent flexibility and can form a network structure inside the artificial stone, effectively dispersing and transmitting stress, reducing the concentrated stress points caused by external forces, thereby enhancing the flexibility and crack resistance of the artificial stone and ensuring the overall strength of the artificial stone. DETAILED DESCRIPTION

[0033] The technical solution provides a high-strength artificial stone obtained by carbonation curing and solidification of artificial stone slurry;

[0034] Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 2-10 parts of cement, 70-120 parts of calcium magnesium sand, 0.04-0.12 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 0-10 parts of silica fume, 1-2 parts of fiber and 8-10 parts of water;

[0035] The chemical components of the steel slag include silicon dioxide, magnesium oxide and calcium oxide; the mineral components of the steel slag include tricalcium silicate, beta-type dicalcium silicate, gamma-type dicalcium silicate, free calcium oxide and free magnesium oxide.

[0036] In view of the technical problem that the artificial stone obtained by using steel slag in the prior art has poor strength and a rough surface, this technical solution proposes a high-strength artificial stone. By designing the proportion of artificial stone slurry and optimizing the raw materials, the artificial stone not only has a delicate and smooth surface, but also has high strength, which meets the actual use needs.

[0037] Specifically, the free calcium oxide and free magnesium oxide in steel slag have low hydration activity and high content. Their continuous slow hydration in the environment not only causes delayed expansion and cracking of artificial stone, bringing serious volume stability problems, but also will lead to the inability to fully utilize the free calcium oxide and free magnesium oxide in the steel slag, affecting the strength of the artificial stone.

[0038] The raw materials of artificial stone slurry in this technical solution include steel slag, cement, calcium magnesium sand, calcium carbonate whisker, polyphosphate, silica fume, fiber and water; the chemical composition of steel slag includes silicon dioxide, magnesium oxide and calcium oxide. Firstly, since calcium oxide in steel slag mainly exists in the form of free calcium oxide, magnesium oxide mainly exists in the form of free magnesium oxide, and free calcium oxide reacts in a water environment to form calcium hydroxide, free magnesium oxide reacts in an aqueous environment to form magnesium hydroxide, which increases the alkalinity of the slurry. During carbonation curing, gaseous CO2 quickly dissolves in the slurry to form carbonic acid, which then dissociates to form bicarbonate ions and carbonate ions; calcium hydroxide generated by free calcium oxide in an aqueous environment reacts with bicarbonate ions / carbonate ions to form calcium carbonate crystals, and magnesium hydroxide generated by free magnesium oxide in an aqueous environment reacts with bicarbonate ions / carbonate ions to form magnesium carbonate crystals, so that free calcium oxide and free magnesium oxide in the steel slag are quickly and massively eliminated, thereby not only eliminating the hidden danger of delayed expansion and cracking caused by the slow hydration of free calcium oxide and free magnesium oxide, but also the generated calcium carbonate crystals and magnesium carbonate crystals can improve the strength of artificial stone by filling pores and compacting the matrix. In addition, in an aqueous environment, the mineral components of the steel slag, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate, can react with bicarbonate ions / carbonate ions to form silica gel, which can better wrap and bond the calcium-magnesium sand aggregate in the artificial stone slurry formula to improve the strength of the artificial stone.

[0039] In addition, although carbonation can make tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, Ca in free calcium oxide 2+ and free magnesium in oxide 2+ A large amount of Ca in the slag participates in the reaction. 2+ and Mg 2+ The dissolution degree is limited, and it is still difficult to fully participate in the carbonation reaction, resulting in insufficient carbonation of the steel slag. The strength of the obtained artificial stone is limited and it is difficult to meet the actual use requirements. 2+ and Mg 2+ As much as possible, the technical solution specifically adds polyphosphate to the artificial stone slurry formula. Polyphosphate acts as a complexing agent, which can react with Ca 2+ and Mg 2+ Complexation weakens the Ca-O and Mg-O bonds in the slag mineral components and promotes Ca 2+ and Mg 2+ The dissolution in the slurry makes the Ca in the slag 2+ and Mg 2+ Participate in the carbonation reaction as much as possible, improve its carbonation degree, and thus increase the strength of artificial stone, while also further eliminating problems such as delayed expansion and cracking caused by the slow hydration of free calcium oxide and free magnesium oxide.

[0040] Furthermore, in order to increase the Ca content in steel slag 2+ and Mg 2+ The dissolution degree can be increased, thereby further improving the strength of the artificial stone. The technical solution adds silica fume to the artificial stone slurry formula. The silicon dioxide in the silica fume is in a tiny spherical shape and has a high reaction activity. It can not only react with the calcium hydroxide generated by free calcium oxide, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate in the steel slag in an aqueous environment to generate hydrated calcium silicate gel, but also react with the magnesium hydroxide generated by free magnesium oxide in an aqueous environment to generate hydrated magnesium silicate gel. The hydrated calcium silicate gel and the hydrated magnesium silicate gel can better wrap and bond the calcium-magnesium sand aggregate in the artificial stone slurry formula, which is beneficial to improving the strength of the artificial stone.

[0041] Furthermore, although the carbonation of steel slag and the increase of Ca in steel slag 2+ and Mg 2+ The dissolution degree is conducive to improving the strength of artificial stone, but the strength of the obtained artificial stone is limited and it is still difficult to meet the actual use requirements. In order to improve the strength of artificial stone, the technical solution also adds cement to the formula, and uses the rapid hydration reaction of cement after contact with water to generate hydrated calcium sulfoaluminate gel and hydrated sodium sulfoaluminate gel. The hydrated calcium sulfoaluminate gel and the hydrated sodium sulfoaluminate gel are well wrapped and bonded to the calcium and magnesium sand in the artificial stone slurry formula, thereby greatly improving the strength of artificial stone. In addition, calcium hydroxide, another hydration product of cement, can also react with silicon dioxide in silica fume to generate hydrated calcium silicate gel. The hydrated calcium silicate gel is used to better wrap and bond the calcium and magnesium sand in the artificial stone slurry formula, which is also conducive to improving the strength of artificial stone. In addition, the rapid hydration property of cement is also conducive to improving the early strength of artificial stone, thereby reducing the breakage rate of artificial stone during transportation before carbonation curing and improving the yield rate.

[0042] Furthermore, although the carbonation of steel slag and the hydration of cement are beneficial to improving the strength of artificial stone, when the strength is too high and the toughness is insufficient, it is easy to cause the artificial stone to break under the action of external force. Therefore, the technical solution also adds fiber to the raw material formula of artificial stone slurry. The fiber itself has excellent flexibility and can form a mesh structure inside the artificial stone, effectively dispersing and transmitting stress, reducing the concentrated stress points caused by external forces, thereby enhancing the flexibility and crack resistance of the artificial stone and ensuring the overall strength of the artificial stone.

[0043] Thirdly, due to the irregular particle size and shape of steel slag, and the fact that steel slag easily forms uneven crystals during the carbonation process, the surface of the artificial stone is relatively rough, affecting the aesthetics and use effect. Therefore, the technical solution also adds calcium carbonate whiskers to the raw material formula of the artificial stone slurry. As a fine needle-shaped material, calcium carbonate whiskers have a high aspect ratio and specific surface area. In the preparation process of artificial stone, they can not only effectively prevent crack expansion, which is beneficial to improving the crack resistance of artificial stone, but also can be used as crystal seeds to provide growth sites for calcium carbonate crystals and magnesium carbonate crystals produced by the carbonation of steel slag, forming a dense skeleton structure, thereby effectively overcoming the technical problem of the rough surface of artificial stone caused by the irregular particle size and shape of steel slag.

[0044] In addition, silica fume can be filled in the gaps between steel slag powder particles to improve density, and calcium carbonate crystals, magnesium carbonate crystals, silica gel, hydrated magnesium silicate gel, hydrated calcium silicate gel, hydrated calcium sulfoaluminate gel and hydrated sodium sulfoaluminate gel generated during the reaction process can wrap calcium magnesium sand to form crystals, which can be filled in artificial stone, which is also conducive to improving the density of artificial stone. The above two aspects of improving density can enhance the fineness and smoothness of artificial stone. In addition, the polyphosphate in the formula can also guide the growth of the above crystals, so that the artificial stone has a more uniform and dense microstructure, further ensuring the fineness and smoothness of the artificial stone.

[0045] Finally, the artificial stone slurry includes the following raw materials, calculated by weight: 40-60 parts of steel slag, 2-10 parts of cement, 70-120 parts of calcium magnesium sand, 0.04-0.12 parts of calcium carbonate whisker, 0.01-0.03 parts of polyphosphate, 0-10 parts of silica fume, 1-2 parts of fiber and 8-10 parts of water. By controlling the addition amount of each component in the artificial stone slurry within a more preferred range, the performance of the artificial stone is better and meets the use requirements.

[0046] Preferably, the cement is high-belite sulphoaluminate cement.

[0047] Compared with other types of cement, high-belite sulphoaluminate cement can quickly generate a large amount of hydration products and produce strength. The above hydration products have excellent filling and bonding properties, can fill the pores and cracks in artificial stone, improve the density of artificial stone, and help improve its fineness, smoothness and strength.

[0048] Preferably, the artificial stone slurry further comprises a silane coupling agent;

[0049] Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 2-10 parts of cement, 70-120 parts of calcium magnesium sand, 0.04-0.12 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 2-10 parts of silica fume, 1-2 parts of fiber, 0.01-0.05 parts of silane coupling agent and 8-10 parts of water.

[0050] In the technical solution, a silane coupling agent is added to the artificial stone slurry to improve the interfacial bonding force between the fiber and other raw materials, thereby ensuring the effective distribution and enhancement effect of the fiber in the artificial stone.

[0051] Preferably, the silane coupling agent includes any one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0052] Further, the particle size of the steel slag is less than 75 μm, and the specific surface area is greater than 350 m 2 / g.

[0053] The smaller the particle size of the steel slag, the larger the specific surface area, which is more conducive to increasing the contact area between the steel slag and CO2, thereby increasing the degree of the steel slag carbonation reaction; at the same time, a smaller particle size and a larger specific surface area are also conducive to improving the fineness and smoothness of the surface of the artificial stone. However, when the particle size is further reduced and the specific surface area is increased, the improvement effect is limited and the production cost is easily increased. Therefore, in this technical solution, the particle size of the steel slag is limited to <75μm and the specific surface area is limited to >350m 2 / g, which is beneficial to improve the strength and surface smoothness of artificial stone at a lower cost.

[0054] It is further explained that, calculated by mass percentage, the chemical composition of the steel slag includes 12-14% silicon dioxide, 40-45% calcium oxide, 3-5% magnesium oxide, 3-5% aluminum oxide, 20-25% iron oxide, 4-6% manganese oxide, 1-2% titanium dioxide, 0-1% potassium oxide and 2-4% phosphorus pentoxide.

[0055] The present technical solution preferably adds steel slag having a calcium oxide content of 40-45% and a magnesium oxide content of 3-5% calculated by mass percentage to the artificial stone slurry formula, so that the total content of calcium oxide and magnesium oxide in the artificial stone slurry formula reaches 43-50%, which is beneficial to increase the carbonation degree of the steel slag, thereby promoting the improvement of the strength of the artificial stone.

[0056] Preferably, calculated by mass percentage, the chemical composition of the steel slag includes 13.8% silicon dioxide, 43.6% calcium oxide, 4.8% magnesium oxide, 4.1% aluminum oxide, 24.6% iron oxide, 5.2% manganese oxide, 1.1% titanium dioxide, 0.5% potassium oxide and 2.3% phosphorus pentoxide.

[0057] It is further specified that the fibers include steel fibers, mineral fibers and organic fibers;

[0058] The mineral fibers include any one or more combinations of chopped basalt fibers, glass fibers and carbon fibers;

[0059] The organic fiber includes any one or more combinations of polyethylene fiber, polypropylene fiber, polyoxymethylene fiber and polyester fiber.

[0060] Steel fiber is known for its high modulus and tensile strength, which can significantly improve the bending, tensile and compressive strength of artificial stone. Mineral fibers such as chopped basalt fibers, glass fibers and carbon fibers also have excellent mechanical properties and can enhance the overall strength and toughness of the material. Although organic fibers such as polyethylene fibers and polypropylene fibers have relatively low strength, they can also improve the toughness of the material to a certain extent and prevent brittle fracture. Therefore, the technical solution is conducive to ensuring the reinforcement and toughening effect of the fibers by limiting the fibers to steel fibers, mineral fibers and organic fibers. In addition, the types of mineral fibers and organic fibers are preferably multiple, and on the premise of ensuring actual needs, suitable raw materials can be selected according to actual needs, which provides more possibilities and flexibility for its application.

[0061] Further description, calculated by mass percentage, the calcium-magnesium sand includes 0-30% of Class I sand of 26-40 mesh, 40-60% of Class II sand of 40-70 mesh, 15-30% of Class III sand of 70-120 mesh and 10-25% of Class IV sand of 120-200 mesh.

[0062] In the technical solution, the mesh size and proportion of various types of sand materials are optimized, which is beneficial to improving the density of artificial stone, thereby improving its strength and surface fineness and smoothness.

[0063] To further illustrate, the polyphosphate includes any one of sodium pyrophosphate, potassium pyrophosphate, sodium tripolyphosphate, potassium tripolyphosphate, sodium hexametaphosphate and potassium hexametaphosphate.

[0064] By preferably selecting a plurality of types of polyphosphate, it is possible to select suitable raw materials according to actual needs while ensuring the performance of artificial stone, thereby providing more possibilities and flexibility for its application.

[0065] Further, according to the mass ratio, the mixing ratio of water to cement in the artificial stone slurry is (0.1-0.14):1;

[0066] The mixing ratio of calcium magnesium sand to cement in the artificial stone slurry is (0.8-1.5):1.

[0067] This technical solution limits the mixing ratio of water and cement (i.e., the water-cement ratio) and the mixing ratio of calcium-magnesium sand and cement (i.e., the sand-cement ratio) in the artificial stone slurry, which not only ensures the fluidity of the artificial stone slurry and makes it easy to construct, but also helps to improve its strength and fine smoothness after solidification.

[0068] A method for preparing high-strength artificial stone, used for preparing the above-mentioned fine, smooth and high-strength artificial stone, comprises the following steps:

[0069] A. dissolving a formulated amount of cement, calcium carbonate whiskers, and silica fume in a part of the formulated amount of water, and stirring evenly to obtain a first mixture;

[0070] B. uniformly mixing the remaining amount of water and polyphosphate to obtain a second mixture;

[0071] C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly;

[0072] D. Pour the artificial stone slurry into the mold and press it into shape to obtain the intermediate product;

[0073] E. The intermediate product is subjected to carbonation curing and then solidified to obtain a high-strength artificial stone, wherein the thickness of the artificial stone is 10 to 40 mm, the compressive strength is ≥130 MPa, and the flexural strength is ≥22 MPa.

[0074] The technical solution also proposes a method for preparing high-strength artificial stone, which has simple steps and strong operability, and is conducive to ensuring the relevant properties of the artificial stone during the preparation process.

[0075] Specifically, the traditional artificial stone must be at least 90 mm to ensure the realization of the excellent performance of the artificial stone. However, if the artificial stone slurry of the present technical solution is used to prepare the artificial stone, its thickness only needs to reach 10 to 40 mm to achieve a compressive strength of ≥130 MPa and a flexural strength of ≥22 MPa, which greatly saves costs.

[0076] Further description, in step E, the curing temperature of the carbonation curing is 40-80°C, the curing time is 2-72h, the curing pressure is 0.1-0.4MPa, and the purity of CO2 is 20-99.9%.

[0077] When the curing temperature, curing pressure and purity of CO2 are too high, the carbonation rate will be too fast, the surface of the artificial stone will be densified too early, and the deep penetration of CO2 will be hindered; when the curing temperature, curing pressure and purity of CO2 are too low, the reaction rate will be too slow, affecting the production efficiency. In order to improve the degree of carbonation reaction, the curing temperature of carbonation curing is specifically limited to 40-80°C, the curing pressure is limited to 0.1-0.4MPa, and the purity of CO2 is limited to 20-99.9%, ensuring that CO2 can fully penetrate into the interior of the artificial stone, improve the degree of carbonation reaction, ensure production efficiency and reduce production costs while ensuring the strength of the artificial stone.

[0078] Furthermore, when the curing time is insufficient, the carbonation degree will decrease; when the curing time is too long, the carbonation degree will not increase significantly, and the production efficiency will be easily reduced. Therefore, the technical solution limits the curing time to 2 to 72 hours, so that the production efficiency can be improved while increasing the carbonation degree and the strength of the artificial stone.

[0079] Further, in step D, the pressure of the pressing molding is 8 to 25 MPa.

[0080] When the pressure during the press molding process is too low, the artificial stone slurry cannot be fully compacted, resulting in more gaps and loose areas inside the artificial stone, which not only affects the fineness and smoothness of the artificial stone, but also reduces its overall strength; when the pressure of the press molding is too high, the fineness and smoothness and strength of the artificial stone are not significantly improved, and the production requirements are high, which is easy to increase the production cost. Therefore, the technical solution limits the pressure of the press molding to ensure its performance at a lower cost and higher production efficiency.

[0081] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0082] Example 1

[0083] In this embodiment, the artificial stone slurry includes the following raw materials calculated by weight: 40 parts of steel slag, 3 parts of cement, 80 parts of calcium magnesium sand, 0.06 parts of calcium carbonate whisker, 0.01 parts of polyphosphate, 4 parts of silica fume, 1 part of fiber and 8 parts of water; the particle size of the steel slag is 50 μm, and the specific surface area is 370 m 2 / g; calculated by mass percentage, the chemical composition of the steel slag includes 13.8% silicon dioxide, 43.6% calcium oxide, 4.8% magnesium oxide, 4.1% aluminum oxide, 24.6% ferric oxide, 5.2% manganese oxide, 1.1% titanium dioxide, 0.5% potassium oxide and 2.3% phosphorus pentoxide; the mineral components of the steel slag include tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide and free magnesium oxide; the cement is high belite sulphoaluminate cement; the fiber includes steel fiber, chopped basalt fiber and polyethylene fiber mixed in a mass ratio of 1:1:1; the polyphosphate is potassium tripolyphosphate; calculated by mass percentage, the calcium-magnesium sand includes 10% of Class I sand of 26-40 mesh, 40% of Class II sand of 40-70 mesh, 30% of Class III sand of 70-120 mesh and 20% of Class IV sand of 120-200 mesh.

[0084] The method for preparing the high-strength artificial stone in this embodiment comprises the following steps:

[0085] A. Dissolve the formulated amount of cement, calcium carbonate whisker and silica fume in 40% of the formulated amount of water, and stir evenly to obtain a first mixture;

[0086] B. Evenly mix 60% of the water and the polyphosphate to obtain a second mixture;

[0087] C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly;

[0088] D. Pour the artificial stone slurry into the mold and press it under a pressure of 15MPa to obtain an intermediate product;

[0089] E. The intermediate product is subjected to carbonation curing at a curing temperature of 40° C., a curing time of 48 h, a curing pressure of 0.2 MPa, and a CO2 purity of 40%, and then solidified to obtain a high-strength artificial stone.

[0090] Example 2

[0091] In this embodiment, the artificial stone slurry includes the following raw materials calculated by weight: 50 parts of steel slag, 5 parts of cement, 80 parts of calcium magnesium sand, 0.06 parts of calcium carbonate whisker, 0.03 parts of polyphosphate, 5 parts of silica fume, 1.5 parts of fiber and 8-10 parts of water; the particle size of the steel slag is 40 μm, and the specific surface area is 400 m 2 / g; calculated by mass percentage, the chemical composition of the steel slag includes 13.8% silicon dioxide, 43.6% calcium oxide, 4.8% magnesium oxide, 4.1% aluminum oxide, 24.6% ferric oxide, 5.2% manganese oxide, 1.1% titanium dioxide, 0.5% potassium oxide and 2.3% phosphorus pentoxide; the mineral components of the steel slag include tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide and free magnesium oxide; the cement is high belite sulphoaluminate cement; the fiber includes steel fiber, glass fiber and polypropylene fiber mixed in a mass ratio of 1:1:1; the polyphosphate is sodium pyrophosphate; calculated by mass percentage, the calcium-magnesium sand includes 20% of Class I sand of 26-40 mesh, 50% of Class II sand of 40-70 mesh, 15% of Class III sand of 70-120 mesh and 15% of Class IV sand of 120-200 mesh.

[0092] The method for preparing the high-strength artificial stone in this embodiment comprises the following steps:

[0093] A. Dissolve the formulated amount of cement, calcium carbonate whisker and silica fume in 40% of the formulated amount of water, and stir evenly to obtain a first mixture;

[0094] B. Evenly mix 60% of the water and the polyphosphate to obtain a second mixture;

[0095] C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly;

[0096] D. Pour the artificial stone slurry into the mold and press it under a pressure of 12MPa to obtain an intermediate product;

[0097] E. The intermediate product is subjected to carbonation curing at a curing temperature of 50° C., a curing time of 24 h, a curing pressure of 0.3 MPa, and a CO2 purity of 50%, and then solidified to obtain a high-strength artificial stone.

[0098] Example 3

[0099] In this embodiment, the artificial stone slurry includes the following raw materials calculated by weight: 60 parts of steel slag, 8 parts of cement, 100 parts of calcium magnesium sand, 0.08 parts of calcium carbonate whisker, 0.03 parts of polyphosphate, 8 parts of silica fume, 2 parts of fiber and 10 parts of water; the particle size of the steel slag is 30 μm, and the specific surface area is 430 m 2 / g; calculated by mass percentage, the chemical composition of the steel slag includes 13.8% silicon dioxide, 43.6% calcium oxide, 4.8% magnesium oxide, 4.1% aluminum oxide, 24.6% ferric oxide, 5.2% manganese oxide, 1.1% titanium dioxide, 0.5% potassium oxide and 2.3% phosphorus pentoxide; the mineral components of the steel slag include tricalcium silicate, β-type dicalcium silicate, γ-type dicalcium silicate, free calcium oxide and free magnesium oxide; the cement is high belite sulphoaluminate cement; the fiber includes steel fiber, carbon fiber and polyoxymethylene fiber mixed in a mass ratio of 1:1:1; the polyphosphate is sodium hexametaphosphate; calculated by mass percentage, the calcium-magnesium sand includes 30% of Class I sand of 26-40 mesh, 40% of Class II sand of 40-70 mesh, 20% of Class III sand of 70-120 mesh and 10% of Class IV sand of 120-200 mesh.

[0100] The method for preparing the high-strength artificial stone in this embodiment comprises the following steps:

[0101] A. Dissolve the formulated amount of cement, calcium carbonate whisker and silica fume in 50% of the formulated amount of water, and stir evenly to obtain a first mixture;

[0102] B. Evenly mix 50% of the water in the formula with the polyphosphate to obtain a second mixture;

[0103] C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly;

[0104] D. Pour the artificial stone slurry into the mold and press it under a pressure of 20MPa to obtain an intermediate product;

[0105] E. The intermediate product is subjected to carbonation curing at a curing temperature of 60° C., a curing time of 60 h, a curing pressure of 0.1 MPa, and a CO2 purity of 30%, and then solidified to obtain a high-strength artificial stone.

[0106] Comparative Example 1

[0107] The preparation method and raw materials of Comparative Example 1 are the same as those of Example 2, except that no steel slag is added to the artificial stone slurry formula in Comparative Example 1.

[0108] Comparative Example 2

[0109] The preparation method and raw materials of Comparative Example 2 are the same as those of Example 2, except that no polyphosphate is added to the artificial stone slurry formula in Comparative Example 2.

[0110] Comparative Example 3

[0111] The preparation method and raw materials of Comparative Example 3 are the same as those of Example 2, except that no silica fume is added to the artificial stone slurry formula in Comparative Example 3.

[0112] Comparative Example 4

[0113] The preparation method and raw materials of Comparative Example 4 are the same as those of Example 2, except that no calcium carbonate whiskers are added to the artificial stone slurry formula in Comparative Example 4.

[0114] Artificial stones were prepared by the preparation methods in the above embodiments and comparative examples, respectively. The thickness of the artificial stones was measured using a vernier caliper. The flexural strength and compressive strength of the artificial stones were tested using the test standard of "GB / T 35160 Test Methods for Synthetic Stones". The surface of the artificial stones was observed with the naked eye, and the results are shown in Table 1 below.

[0115] Table 1 Test results of relevant properties of artificial stone

[0116]

[0117] From the performance test results in Table 1, it can be seen that the technical solution provides a high-strength artificial stone with a compressive strength of ≥130MPa and a flexural strength of ≥22MPa. It not only has a fine and smooth surface, but also has high strength, which meets the use requirements.

[0118] In Comparative Example 1, since no steel slag is added, the strength of the artificial stone slurry is deteriorated, thereby affecting the strength of the artificial stone.

[0119] Comparative Example 2: Since no polyphosphate was added, the Ca content in the steel slag was 2+ and Mg 2+ The carbonation reaction is limited, resulting in insufficient carbonation of the steel slag, which affects the strength of the artificial stone. In addition, the lack of polyphosphate also results in the inability to guide the growth of the crystals, affecting the fineness and smoothness of the artificial stone.

[0120] In Comparative Example 3, since no silica fume is added, it is impossible to utilize the calcium hydroxide generated by the reaction of silica fume with free calcium oxide, tricalcium silicate, β-type dicalcium silicate and γ-type dicalcium silicate in the steel slag in an aqueous environment to generate calcium silicate hydrate gel. At the same time, it is also impossible to utilize the reaction of silica fume with free magnesium oxide in an aqueous environment to generate magnesium hydroxide to generate magnesium silicate hydrate gel, resulting in reduced strength and fine smoothness of the artificial stone.

[0121] Since no calcium carbonate whiskers were added in Comparative Example 4, it was unable to fill the voids in the artificial stone, prevent the cracks from expanding, and provide growth sites for calcium carbonate and magnesium carbonate produced by the carbonation of steel slag, thereby affecting the strength and fine smoothness of the artificial stone.

[0122] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific implementations of the present invention without paying creative labor, and these methods will fall within the scope of protection of the present invention.

Claims

1. A high-strength artificial stone, characterized in that: Obtained by carbonation, curing and solidification of artificial stone slurry; Calculated by weight, the artificial stone slurry includes the following raw materials: 40-60 parts of steel slag, 2-10 parts of cement, 70-120 parts of calcium magnesium sand, 0.04-0.12 parts of calcium carbonate whiskers, 0.01-0.03 parts of polyphosphate, 0-10 parts of silica fume, 1-2 parts of fiber and 8-10 parts of water; The chemical components of the steel slag include silicon dioxide, magnesium oxide and calcium oxide; the mineral components of the steel slag include tricalcium silicate, beta-type dicalcium silicate, gamma-type dicalcium silicate, free calcium oxide and free magnesium oxide.

2. The high-strength artificial stone according to claim 1, characterized in that: The particle size of the steel slag is less than 75 μm, and the specific surface area is greater than 350 m 2 / g.

3. The high-strength artificial stone according to claim 1, characterized in that: Calculated by mass percentage, the chemical composition of the steel slag includes 12-14% silicon dioxide, 40-45% calcium oxide, 3-5% magnesium oxide, 3-5% aluminum oxide, 20-25% iron oxide, 4-6% manganese oxide, 1-2% titanium dioxide, 0-1% potassium oxide and 2-4% phosphorus pentoxide.

4. The high-strength artificial stone according to claim 1, characterized in that: The fibers include steel fibers, mineral fibers and organic fibers; The mineral fibers include any one or more combinations of chopped basalt fibers, glass fibers and carbon fibers; The organic fiber includes any one or more combinations of polyethylene fiber, polypropylene fiber, polyoxymethylene fiber and polyester fiber.

5. The high-strength artificial stone according to claim 1, characterized in that: Calculated by mass percentage, the calcium-magnesium sand includes 0-30% of Class I sand of 26-40 meshes, 40-60% of Class II sand of 40-70 meshes, 15-30% of Class III sand of 70-120 meshes and 10-25% of Class IV sand of 120-200 meshes.

6. The high-strength artificial stone according to claim 1, characterized in that: The polyphosphate includes any one of sodium pyrophosphate, potassium pyrophosphate, sodium tripolyphosphate, potassium tripolyphosphate, sodium hexametaphosphate and potassium hexametaphosphate.

7. The high-strength artificial stone according to claim 1, characterized in that: Calculated by mass ratio, the mixing ratio of water to cement in the artificial stone slurry is (0.1-0.14):1; The mixing ratio of calcium magnesium sand to cement in the artificial stone slurry is (0.8-1.5):

1.

8. A method for preparing high-strength artificial stone, characterized in that: The method for preparing the fine, smooth and high-strength artificial stone as claimed in any one of claims 1 to 7 comprises the following steps: A. dissolving a formulated amount of cement, calcium carbonate whiskers, and silica fume in a part of the formulated amount of water, and stirring evenly to obtain a first mixture; B. uniformly mixing the remaining amount of water and polyphosphate to obtain a second mixture; C. After the first mixture, the second mixture, the formula amount of steel slag and calcium magnesium sand are mixed evenly, the formula amount of fiber is added, and the artificial stone slurry is obtained after stirring evenly; D. Pour the artificial stone slurry into the mold and press it into shape to obtain the intermediate product; E. The intermediate product is subjected to carbonation curing and then solidified to obtain a high-strength artificial stone, wherein the thickness of the artificial stone is 10 to 40 mm, the compressive strength is ≥130 MPa, and the flexural strength is ≥22 MPa.

9. The high-strength artificial stone according to claim 8, characterized in that: In step E, the curing temperature of the carbonation curing is 40-80° C., the curing time is 2-72 hours, the curing pressure is 0.1-0.4 MPa, and the purity of CO2 is 20-99.9%.

10. The high-strength artificial stone according to claim 8, characterized in that: In step D, the pressure of the compression molding is 8 to 25 MPa.

Citation Information

Patent Citations

  • Anti-efflorescence paving stone and preparation method thereof

    CN117447143A

Cited By

  • High-toughness saltpetering-preventing artificial stone plate and preparation method thereof

    CN120058293A

  • High-toughness artificial stone panel for preventing efflorescence and method for manufacturing the same

    CN120058293B